Task Intelligence Workshop @ WSDM 2019 - Awadallah, Ahmed; Gurrin, Cathal; Sanderson, Mark; White, Ryen W. (The International Conference on Web Search and Data Mining (WSDM 2019)., 2019)
The task intelligence workshop at the 2019 ACM Web Search and Data Mining (WSDM) conference comprised a mixture of research paper presentations, reports from data challenge participants, invited keynote(s) on broad topics related to tasks, and a workshop wide discussion about task intelligence and its implications for system development.